POLA ASUH ORANGTUA TUNGGAL (STUDI KASUS DI DESA TELUK KAPUAS KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA) - Natalia, Eta; Zakso, Amrazi; Alhidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of the research was "Parenting Single Parenting (Case Study in DesaTeluk Kapuas Kecamatan Sungai Raya KabupatenKubu Raya)". The research method used was a qualitative research method with descriptive research type. The data source of this research was a single parent who is in the village of Teluk Kapuas. Data collection techniques through interviews, observation and documentation, data collection tools were observation guides, interview guides and documentation tools. The analysis in this study was presented in a descriptive qualitative manner, using 8 informants namely, 3 single parents and 5 children from the single parent. The results of his research that (1) Parenting applied by single parents is more dominant with democratic parenting patterns. Itwas proven by parents encouraging children to be open as expressed their opinions, there was good cooperation between parents and children in carrying out activities, there was guidance and direction from parents about good and bad deeds, as well as controls or supervision conducted by parents who were not rigid to children. (2) The impact of parenting that was applied by a single parent gives a positive impact; the child is more confident because it was given support by his parents, cares about the environment inside and outside the home and makes his parents a role model for him.Keywords: Parenting, Single Parents